Early Mobilization in Aneurysmal Subarachnoid Hemorrhage Accelerates Recovery and Reduces Length of Stay. Issue 2 (August 2015) - Olkowski, Brian F.; Binning, Mandy J.; Sanfillippo, Geri; Arcaro, Melissa L.; Slotnick, Laurie E.; Veznedaroglu, Erol; Liebman, Kenneth M.; Warren, Amy E.
Abstract : Background: Survivors of aneurysmal subarachnoid hemorrhage (SAH) are faced with a complicated recovery, which typically includes surgery, prolonged monitoring in the intensive care unit (ICU), and treatment focusing on the prevention of complications. The early mobilization of patients with aneurysmal has been determined to be safe and feasible. Purpose: The purpose of this study was to determine whether an early mobilization program for patients with aneurysmal SAH has an effect on function and hospital length of stay. Methods: A retrospective review of patients admitted to the neurosurgical ICU with a diagnosis of aneurysmal SAH was conducted. Fifty-five patients composed the early mobility group and were assessed daily by a physical therapist and/or occupational therapist to determine whether criteria were met to participate in the early mobilization program. Early mobilization program sessions were conducted by physical and/or occupational therapists and focused on positioning, education, functional training, and therapeutic exercise in the supine, sitting, standing, and walking positions. Thirty-eight patients admitted to the neurosurgical ICU before the implementation of the early mobility program composed a historical control group. Results: The number of physical and occupational therapy sessions was similar for both groups. Patients receiving early mobilization participated in 2.1 more sessions that included out-of-bed (OOB) activity when compared with the control group ( P = .013). In addition, patients participated in OOB activity 2.2 days sooner ( P = .039), walked 50 ft 4.1 days sooner ( P = .004) and were discharged from the hospital 2.9 days sooner ( P = .013) than patients who did not receive early mobilization. Conclusion: Patients with aneurysmal SAH receiving early mobilization in the ICU can return to OOB activity and walking sooner and are discharged from the hospital faster. In addition, patients receiving early mobilization participated in more functional activities during physical and occupational therapy sessions.